Limit cycles in a Kolmogorov-type model - Xun-Cheng Huang (International Journal of Mathematics and Mathematical Sciences)
In this paper, a Kolmogorov-type model, which includes the Gause-type model (Kuang and Freedman, 1988), the general predator-prey model (Huang 1988, Huang and Merrill 1989), and many other specialized models, is studied. The stability of equilibrium points, the existence and uniqueness of limit cycles in the model are proved.